ELECTIONS AND THE DIGITAL CAMPAIGN CODE OF ETHICS: EFFORTS TO CREATE A CAMPAIGN BASED ON DIGNIFIED JUSTICE - Razak, Askari; Amin, Fakhry (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Elections, as a cornerstone of democracy, are encountering unprecedented challenges in maintaining ethical standards and justice values, primarily due to the surge in digital campaigning. Ethical concerns arising from the unregulated use of digital campaign media underscore the urgent need to formulate and implement a Digital Campaign Code of Ethics. This code is envisioned as a guide to integrity for political communicators in the digital space. The research explores the imperative nature of establishing a digital campaign code of ethics to foster responsible election campaigns reflective of justice and dignity. It also seeks to identify challenges and obstacles associated with its implementation. Using a legislative and conceptual approach, this normative legal research scrutinizes regulations related to elections and campaigns, reviewing legal doctrines and principles pertinent to forming a digital campaign code of ethics. Primary and secondary legal materials are collected, analyzed descriptively and analytically, and formulated into logical arguments to address legal issues. The findings emphasize the critical urgency of a digital campaign code of ethics in realizing responsible election campaigns aligned with justice and dignity. The prevalence of digital media and social networks as primary campaign channels heightens the risk of these campaigns becoming tools to advance specific interests without considering justice. The code of ethics is deemed essential to provide legal certainty, delineate ethical boundaries, and prevent the misuse of digital media. Additionally, it guides campaign participants to engage in political competition with integrity and dignity. However, the challenges associated with implementing digital ethics codes are complex. Control over ethical standards is challenging due to the swift dissemination of campaign content, delayed oversight and sanctions, and social media's vulnerability to misinformation and personal attacks. Active cooperation among authorities, election organizers, and social media platforms is crucial for effective monitoring and response to digital campaign content that violates ethical standards.